Anticyclonic Eddies Enhance the Winter Barrier Layer and Surface Cooling in the Bay of Bengal. Issue 10 (30th September 2020) - He, Qingyou; Zhan, Haigang; Cai, Shuqun
Abstract: Oceanic barrier layer impedes the vertical exchanges of heat and biogeochemical substances between the mixed layer and deep ocean, playing essential roles in modulating air‐sea heat flux and oceanic biogeochemical cycles. Recent studies revealed that mesoscale eddies can modify the vertical motions of the mixed layer. But their influence on the barrier layer has not been determined. By analyzing more than a decade of in situ, satellite, and reanalysis data, this study investigated the influence of eddies on barrier layer in the Bay of Bengal. The results show that the barrier layer in anticyclonic eddies is significantly thickened in winter (by 50% on average). This thickening consists of the deepening of isothermal layer by eddy downwelling and the shoaling of mixed layer by near‐surface salinity restratification. The thickening of the barrier layer enlarges with latitude, in consistent with the reinforcement in salinity stratification and surface cooling. The thickened barrier layer impedes the upward supply of heat into the mixed layer from the below, promoting the winter surface cooling (by 0.7°C on average) and subsurface temperature inversion (by 0.6°C on average). The feature is contrary to the intuitive expectation that anticyclonic eddies possess high sea surface temperature in eddy interiors. As a consequence, both cyclonic and anticyclonic eddies result in negative sea surface temperature anomalies, indicative of a net decrease in the local sea surface temperature. These effects of eddies may be a common feature in salinity‐stratified oceans in winter and have potential implications for the local biogeochemistry and air‐sea coupled models. Key Points: Anticyclonic eddies significantly thicken the barrier layer in the Bay of Bengal in winter This thickening consists of isothermal layer deepening by eddy downwelling and mixed layer shoaling by salinity restratification The thickened barrier layer promotes the winter surface cooling and subsurface temperature inversion Plain Language Summary: Oceanic barrier layer impedes the vertical exchanges of heat and biogeochemical substances between the near‐surface and deep ocean, playing essential roles in modulating sea surface temperature, air‐sea heat flux, and oceanic biogeochemical cycles. Here, we investigated the influence of mesoscale eddies on the barrier layer in the Bay of Bengal. We show that in such salinity‐stratified oceans, anticyclonic eddies significantly thicken the barrier layer in winter. This thickening consists of the deepening of isothermal layer and the shoaling of mixed layer. The thickened barrier layer impedes the upward supply of heat into the mixed layer and retains the heat in the barrier layer, promoting the winter surface cooling and subsurface temperature inversion. As a consequence, sea surface temperature is lower in the eddies compared to the ambient, contrasting to the intuitive expectation that anticyclonic eddies possess high temperature. In addition to the low sea surface temperature in cyclonic eddies, both types of the eddies lead to surface cooling, breaking the standard symmetry of cyclonic versus anticyclonic eddies, whose effects usually cancel each other out. These results may potentially have far‐reaching implications from the local biogeochemistry to climate models which, due to their coarse, non‐eddy‐resolving resolution, are unable to capture this phenomenon.